Retinitis pigmentosa and molar tooth sign caused by novel AHI1 compound heterozygote pathogenic variants - Chunyan Chen; Jiong Gao; Qing Lv; Chen Xu; Yu Xia; Ailian Du (BMC, 2021)
Abstract Background Joubert syndrome (JS) is a group of rare congenital disorders characterized by cerebellar vermis dysplasia, developmental delay, and retina dysfunctions. Herein, we reported a Chinese patient carrying a new variant in the AHI1 gene with mild JS, and the 3D structure of the affected Jouberin protein was also predicted. Case presentation The patient was a 31-year-old male, who presented difficulty at finding toys at the age of 2 years, night blindness from age of 5 years, intention tremor and walking imbalance from 29 years of age. Tubular visual field and retina pigmentation were observed on ophthalmology examinations, as well as molar tooth sign on brain magnetic resonance imaging (MRI). Whole exome sequence revealed two compound heterozygous variants at c.2105C>T (p.T702M) and c.1330A>T (p.I444F) in AHI1 gene. The latter one was a novel mutation. The 3D protein structure was predicted using I-TASSER and PyMOL, showing structural changes from functional β-sheet and α-helix to non-functional D-loop, respectively. Conclusions Mild JS due to novel variants at T702M and I444F in the AHI1 gene was reported. The 3D-structural changes in Jouberin protein might underlie the pathogenesis of JS.